The technique of film editing - Reisz, Karel; Millar, Gavin; Dickinson, Thorold (Oxon : Focal Press, 2014)
"Enhanced version of the seminal text on editing includes a new foreword, a new afterword, a revamped cover and layout!The single most comprehensive and engaging volume on film editing. Reisz and Millar introduce readers to every aspect of the editor's craft, providing a concise history of editing and describing editing style as it applies to every genre of moviemaking, including many types of narrative and documentary films. The particular demands of wide-screen filmmaking, cinema verite, and the avant-garde are also covered.Reisz and Millar's account of the differences between smooth and abrupt editing and their remarkable sense of editing for dramatic effect rather than for realism make this book essential for apprentice editors, as well as those who want to know how filmmakers understand their work."--
Keywords: The British Film Academy; Motion pictures -- Editing; Motion pictures